(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
A wave energy device operates in a wide range of sea states from low load to 4 to 8 times rated load over a wide speed range. Existing PTOs combine mechanical speed enhancers with conventional high speed electrical generator and power converter, with questions over reliability and cannot operate over wide operating ranges. The EU funded MEGA WAVE PTO project is addressing this challenge by developing an all-electric power take off incorporating three sub-systems: a contactless magnetic gear; the modular C-GEN generator; and modular power electronics. The rationale for the technology choice for the all electric power take off is summarised to provide context. An outline of the methodology is presented through six main themes ranging from engineering design, control and testing, to levelized cost, carbon footprint and supply chain analysis, all with the main aim to demonstrate a scalable, reliable and maintainable fully integrated all-electric modular PTO system customized for wave energy devices from kWs to MWs across the Blue Economy sector. Preliminary work from two deliverables completed in the first year are presented to show the design of a 1000 Nm magnetic gear prototype, and a framework for life-cycle assessment of wave devices to understand the potential impact of MEGA WAVE PTO on carbon footprint.